(untitled) (Collection of scientific works «Modern structures of metal and wood», 2020)
Currently, the use of timber building structures has gained great popularity in the world. The appearance of modern types and technologies for the manufacturing of joints of timber structures elements makes it necessary to conduct corresponding studies of its behaviour under load, as well as theoretical and experimental assessment of load-bearing capacity and deformability. The article presents the results of theoretical and experimental studies of the performance of the bolted connection of glued timber elements with metal plates under the action of a tensile load parallel to the fibers. A sample consisting of a glued timber beam 750 mm long with cross-section section dimensions of 120x120 mm and a connecting steel plate embedded in a solid wood was adopted for the study. The joint work of the beam and the plate is ensured by three bolts with a diameter of 12 mm. Glued laminated timber is made of pine wood lumber. The technique for the experiment was developed. As a result of the tests, the actual value of the failure load equal to 113.7 kN was obtained, as well as a diagram of the dependence of the deformation of the sample on the magnitude of the tensile load. The behaviour of the sample under a load up to 80 kN is characterized by a close to linear dependence. At larger values of the load, nonlinear deformations occur due to the bending of the bolts. An analysis of the shape of the bending of the bolts allows suggesting the uniform redistribution of the inner forces of the connection. Taking into account the current design standards, the theoretical bearing capacity of the joint was determined according to the possible forms of failure. The experimental value differs from theoretical by 67.5% and 11.3%, respectively. It is established that the main parameter that has determined the bearing capacity of the connection is the embedment strength of the wood under the surface of the bolt.